The preferred form of payment for university students in Malaysia - Muhammad Badron, Ahmad Shakir; Nor Ramli, Muhammad Faiq; Abd Aziz, Ayzad Daniel; Sanusi, Farhan Iskandar; Ahmad, Nur Intan Syafinaz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
In this modern world with new technology there are many varieties of payment methods that have been made by commercial banks in the world. These are the several types of payment methods including cash, mobile e-wallet, cheque, instant transfer, and cryptocurrencies as the relative newcomers in this modern technology. Since the pandemic started, many businesses take a new step in upgrading their businesses providing new payment method. The percentage of using online transaction increasing due to the urge from the government to encourage Malaysian people to use contact less payments options in response to pandemic concerns. Due to this announcement, almost all university in Malaysia have been introducing online payment for all transaction. Some student are convenient with convention method that is using cash while others are more eager to use online payment in any transaction. Due to this reason, studied has been done to examine the type of payment that is commonly used by students in Malaysia. Based on the finding, students nowadays prefer to make cashless transaction rather than cash. This conclude that students nowadays preferred paying by using QR code payment type as it is easier to use and some of them still carrying cash as for emergency or they just preferred paying by using cash rather than other payment type provided.